Increased attraction and stability of beauveria bassiana-formulated microgranules for aedes aegypti biocontrol - Zamora Avilés, Norma; Orozco Flores, Alonso Alberto; Gomez Flores, Ricardo; Domínguez Gámez, Maribel; Rodríguez Pérez, Mario Alberto; Tamez Guerra, Patricia (Multidisciplinary Digital Publishing Institute, 2022)
Aedes aegypti (Linn.) incidence has increased in recent years, causing human viral diseases such as dengue, which are often fatal. Beauveria bassiana (Bals., Vuillemin) efficacy for Ae. aegypti biological control has been evidenced but it relies on host susceptibility and strain virulence. We hypothesized that B. bassiana conidia microgranular formulations (MGF) with the additives acetone, lactic acid, and sugar increase Ae. aegypti adult exposure, thus improving their biocontrol effectiveness. Beauveria bassiana strain four (BBPTG4) conidia stability was assessed after 0 d, 5 d, and 30 d storage at 25 ◦C ± 2 ◦C with additives or in MGF after 91 d of storage at 25 ◦C ± 2 ◦C or 4 ◦C ± 1 ◦C, whereas mortality was evaluated after adult exposure to MGF + conidia, using home-made traps. Additives did not show toxicity to conidia. In addition, we observed that sugar in MGF increased Ae. aegypti adults’ attraction and their viability resulted in a 3-fold reduction after 5 d and 1- to 4-fold decrease after 30 d of storage, and formulations were less attractive (p < 0.05). Conidia stability was higher on MGF regardless of the storage temperature, losing up to 2.5-fold viability after 91 d. In conclusion, BBPTG4 infected and killed Ae. aegypti, whereas MGF attracting adults resulted in 42.2% mortality, increasing fungus auto dissemination potential among infected surviving adults. It is necessary to further evaluate MGF against Ae. aegypti in the field.